High Disease Severity Among Asian Patients in a US Multiethnic Cohort of Individuals With Systemic Lupus Erythematosus. Issue 6 (20th April 2022) - DeQuattro, Kimberly; Trupin, Laura; Murphy, Louise B.; Rush, Stephanie; Criswell, Lindsey A.; Lanata, Cristina M.; Dall'Era, Maria; Katz, Patricia; Yazdany, Jinoos
Abstract : Objective: Knowledge about systemic lupus erythematosus (SLE) outcomes among US Asian patients is lacking. The present study was undertaken to examine SLE disease activity, severity, and damage among Asian patients of primarily Chinese and Filipino descent in a multiethnic cohort. Methods: California Lupus Epidemiology Study (n = 328) data were analyzed. Data were collected in English, Cantonese, Mandarin, or Spanish using validated instruments for disease activity (Systemic Lupus Erythematosus Disease Activity Index), disease severity (Lupus Severity Index [LSI]), and disease damage (Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index). We assessed differences in SLE outcomes among racial/ethnic groups using multivariable linear regression including interaction terms for age at diagnosis and race/ethnicity. Results: Asian was the largest racial/ethnic group (38% [Chinese = 22%; Filipino = 9%; Other = 7%]). Average age at diagnosis was younger among Asian patients (27.9 years), particularly Filipino patients (22.2 years), compared with White (29.4 years) and Black patients (34.0 years). After adjustment, disease activity and damage were not significantly different across groups. Disease severity among Asian patients was significantly higher than among White patients (LSI score 7.1 versus 6.5; P < 0.05) but similar among Black and Hispanic patients. Early age at diagnosis was associated with greater organ damage among Asian, Black, and Hispanic patients, but not White patients. Conclusion: SLE was more severe among US Asian patients compared to White patients. Filipinos were affected at strikingly young ages. Asian patients and non‐White groups with younger age at diagnosis had greater organ damage than White patients. Such racial/ethnic distinctions suggest the need for heightened clinical awareness to improve health outcomes among Asian patients with SLE. Further study of SLE outcomes across a range of US Asian subgroups is important.